Development of a novel patient-reported measure for acromegaly: the Acro-TSQ - Fleseriu, Maria (Pituitary, 2019)
PURPOSE: Somatostatin analogs (SSAs) represent a mainstay of medical treatment for acromegaly, currently available as either intramuscular or deep subcutaneous injections. Patient-reported outcomes (PROs) are increasingly common as relevant outcomes in studies of acromegaly and its treatment, but there are no validated PRO measures available that focus on the disease burden and the impact of treatment, specifically designed for use in patients with acromegaly. We sought to develop a new and unique PRO measure, the Acromegaly Treatment Satisfaction Questionnaire (Acro-TSQ). METHODS: Concept elicitation (CE) interviews were conducted with acromegaly patients in the United States receiving SSA injections at a stable dose for ≥ 6 months. A questionnaire was drafted based on these interviews; combined CE and cognitive debriefing (CE/CD) interviews were then conducted to confirm the content, clarity, and relevance of the questionnaire. RESULTS: Nineteen subjects completed interviews [n = 9 CE, n = 10 CE/CD; n = 15 Lanreotide Depot/Autogel (Somatuline), n = 4 Octreotide LAR (Sandostatin LAR)]. Most subjects responded positively when asked about the effectiveness of their current treatment; however, breakthrough symptoms, injection site reactions, and side effects were commonly reported and had negative impacts on social and emotional well-being and daily activities. All 10 subjects involved in debriefing interviews found the questionnaire to be relevant, easy to complete, and found the response options to be clear. The resulting 26-item Acro-TSQ covers symptoms and symptom control, gastrointestinal side effects and their impact on daily activities, the emotional impact of treatment, convenience and ease of use, and overall satisfaction. CONCLUSIONS: The Acro-TSQ is a novel PRO, focused on both disease burden and impact of treatment; it was found to be comprehensive, clear, and relevant for patients with acromegaly receiving injectable SSA treatment.